The Impact of Trade Openness, Foreign Direct Investment, Inflation, and the Working-Age Population on Economic Growth in Eight ASEAN Countries - Olivia Adamia Fista; Septriani (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – This study examines the effects of trade openness, foreign direct investment (FDI), inflation, and the working-age population on economic growth in eight ASEAN countries during 2005–2024. The analysis is motivated by disparities in economic performance across ASEAN economies and mixed evidence on the roles of macroeconomic and demographic factors in promoting long-term economic growth. Methods – This quantitative study uses balanced panel data from the World Bank covering eight ASEAN countries during 2005–2024. Panel regression analysis was conducted, with the Chow and Lagrange Multiplier tests selecting the Common Effects Model (CEM) as the appropriate specification. Diagnostic tests were then performed to ensure the robustness of the estimation results. Findings – The results indicate that FDI and inflation have positive and statistically significant effects on economic growth, highlighting the importance of productive capital inflows and macroeconomic stability. Trade openness is positively associated with economic growth but remains statistically insignificant. In contrast, the working-age population has a negative and statistically significant effect, indicating that a larger working-age population does not necessarily lead to higher economic growth. Research implications – The study is limited to eight ATIGA-member ASEAN countries, so the findings cannot be generalized to the region as a whole; the first-difference specification also does not fully resolve endogeneity concerns arising from reverse causality or omitted variables, which should be addressed through more robust estimation methods in future research. Originality – This study contributes to the ASEAN economic growth literature by showing that, under the ASEAN Trade in Goods Agreement (ATIGA), economic growth remains driven by country-specific conditions rather than uniform regional determinants. The findings indicate that the effects of trade openness and demographic structure are conditional across ASEAN economies.